2022
DOI: 10.3389/fpls.2022.930639
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Candidate Genes Underlying Soluble Sugar Content in Vegetable Soybean (Glycine max L.) via Association and Expression Analysis

Abstract: Soluble sugar is a major indicator of the intrinsic quality of vegetable soybean [Glycine max (L.) Merr. ]. The improvement of soluble sugar content in soybean is very important due to its healthcare functions for humans. The genetic mechanism of soluble sugar in soybean is unclear. In this study, 278 diverse soybean accessions were utilized to identify the quantitative trait nucleotides (QTNs) for total soluble sugar content in soybean seeds based on a genome-wide association study (GWAS). A total of 25,921 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…To ensure a global supply of soybean products, the development of high-yield and high-oil cultivars has become the primary breeding target in soybean breeding programs [ 2 ]. Soybean is rich in various primary and secondary metabolites, such as flavonoids, lipids, and sugar metabolites [ 3 , 4 ]. Lipid metabolites play an important role in seed metabolism and are the main carrier for the production of soybean oil [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…To ensure a global supply of soybean products, the development of high-yield and high-oil cultivars has become the primary breeding target in soybean breeding programs [ 2 ]. Soybean is rich in various primary and secondary metabolites, such as flavonoids, lipids, and sugar metabolites [ 3 , 4 ]. Lipid metabolites play an important role in seed metabolism and are the main carrier for the production of soybean oil [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because raffinose and stachyose are derived from sucrose, possibly these two SNPs point to the same QTL. The SNP Gm15_49568824 associated with both sucrose and total sugar content was 293 Kb away from the SNP rs49892059 (Gm15_49892059), which was the peak marker of a QTL for soluble sugar content in a previous study [ 28 ].…”
Section: Discussionmentioning
confidence: 95%
“…Of these genes, one had been reported previously to be associated with sucrose content, while the other nine were considered as novel genes for sucrose content. Lu et al [ 28 ] reported a GWAS on total soluble sugar content in soybean using 278 diverse soybean accessions. They detected 84 SNPs from seventeen genes across four chromosomes to be associated with the total soluble sugar content.…”
Section: Introductionmentioning
confidence: 99%
“…To date, 42 QTLs have been reported for soybean seed sucrose contents through linkage analysis of bi-parental mapping populations (https://www.soybase.org/search/qtllist_by_symbol.php, accessed on February 13, 2023). However, only a few studies involving GWAS have been reported in recent years (Sui et al 2020;Ficht et al 2022;Xu et al 2022;Lu et al 2022). This study also followed GWAS approach to pinpoint important genomic regions signi cantly associated with seed sucrose contents.…”
Section: Stable Snp Markers For Screening Of Soybean Genotypesmentioning
confidence: 99%